2013
DOI: 10.1115/1.4023846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Joint Size on Microstructure and Growth Kinetics of Intermetallic Compounds in Solid-Liquid Interdiffusion Sn3.5Ag/Cu-Substrate Solder Joints

Abstract: The effect of joint size on the interfacial reaction in the Sn3.5Ag/Cu-substrate soldering system was examined. An experiment was conducted in which parameters such as bonding time, temperature, and pressure were varied at multiple levels. The morphology and thickness of all intermetallic compounds (IMC) were analyzed using the scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) techniques. An examination of the microstructures of solder joints of different sizes revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Therefore, the underlying mechanism for the size effects of solder joints is highly likely to be related to the Cu flux. Abdelhadi et al [32] established an analytical model to investigate the growth rate of Cu 3 Sn, which was found to be joint-size dependent and obey the parabolic relation with time. Huang et al [33] measured the IMC evolution of Sn3.0Ag0.5Cu solder joints on Cu or Ni-P pads, and the Cu flux variation was inferred to be the cause of solder volume size effects.…”
Section: Solidification and Recrystallization In The Solder Matrixmentioning
confidence: 99%
“…Therefore, the underlying mechanism for the size effects of solder joints is highly likely to be related to the Cu flux. Abdelhadi et al [32] established an analytical model to investigate the growth rate of Cu 3 Sn, which was found to be joint-size dependent and obey the parabolic relation with time. Huang et al [33] measured the IMC evolution of Sn3.0Ag0.5Cu solder joints on Cu or Ni-P pads, and the Cu flux variation was inferred to be the cause of solder volume size effects.…”
Section: Solidification and Recrystallization In The Solder Matrixmentioning
confidence: 99%
“…6(f), the hydrostatic stress over the entire domain is observed to be tensile, i.e., s H > 0, with the minimum tensile stress located in the region that separates the two Cu 6 Sn 5 grains. The interdiffusion flux tends to flow away from the top boundary and into the region between the two Cu 6 Sn 5 grains, which is driven by the gradient of s H according to (15). Consequently, more Sn atoms are available at the interface between the b-Sn and Cu 3 Sn grains to react and form a new Cu 6 Sn 5 phase.…”
Section: A Effects Of Stress On the Morphology And Growth Rate Of Inmentioning
confidence: 99%
“…Abdelhadi et al reported faster growth of the Cu 3 Sn IMC in smaller Sn3.5Ag solder joints and attributed this result to the effect of stress on the diffusion rates of Sn and Cu. [15]. EM also affects the microstructure within microbumps [17]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…IMCs such as Cu6Sn5 and Cu3Sn form in between solder/Cu interface due to the diffusion of copper (Cu) into bulk solder (Sn). In Cu pillar micro bumps, major portion of bulk Sn converts into IMCs during the diffusion process, and therefore, the Cu pillar bump is typically left with small volume fraction of ductile solder alloy [1,2]. These IMCs are necessary for good metallurgical bonding.…”
Section: Introductionmentioning
confidence: 99%